Network traffic analysis system based on IPFIX - Yun-long MA; Qian-li ZHANG; Ji-long WANG (Tongxin xuebao)
To deal with the large-scale traffic capture and management in high speed network,the performance of IPFIX system was studied.An optimized architecture was proposed and implemented based on improved binary information integration to collect data and improved multi-layer hash algorithm to storage data.This system was deployed in Tsinghua university campus network and can scale to the 10 GB network traffic collection and accurate pricing.